Assessment of Choroidal Microstructure and Subfoveal Thickness Change in Eyes With Different Stages of Age-Related Macular Degeneration. Issue 10 (March 2016) - Lu, Linna; Xu, Shiqiong; He, Fangling; Liu, Yan; Zhang, Yidan; Wang, Jing; Wang, Zhiliang; Fan, Xianqun
Abstract : Abstract: Age-related macular degeneration (AMD) is a major cause of irreversible blindness. Choroidal structural changes seem to be inevitable in AMD pathogenesis. Our study revealed associated choroidal microstructural changes in AMD eyes. The aim of the study was to compare choroidal microstructural changes in eyes with AMD of different stages. The study was a retrospective, cross-sectional case series. The participants comprised of 32 age-matched normal eyes as controls, and 26 fellow uninvolved eyes of intermediate/late AMD, 29 of early AMD, 28 of intermediate AMD, and 39 of late AMD. All subjects underwent comprehensive ophthalmologic examination. The choroid images, including subfoveal choroidal thickness, percentage of Sattler layer area, and en face images of the choroid, were obtained using spectral-domain optical coherence tomography. The main outcome measures were subfoveal choroidal thickness changes, percentage of Sattler layer area changes, and en face images of the choroid in AMD eyes. One hundred fifty-four eyes of 96 individuals with mean age of 67.1±9.2 years were included. The mean subfoveal choroidal thickness was 295.4 ± 56.8 μm in age-matched normal eyes, 306.7 ± 68.4 μm in fellow uninvolved eyes with AMD, 293.8 ± 80.4 μm in early AMD, 215.6 ± 80.4 μm in intermediate AMD, and 200.4 ± 66.6 μm in late AMD ( F = 14.2, all P < 0.001). Choroidal thickness was greater in early AMD eyes than in intermediate/late AMD eyes ( P < 0.001). Mean percentage of Sattler layer area in each group showed a similar tendency. Microstructure of the choroid showed reduced vascular density of Sattler layer areas in late AMD eyes compared with normal eyes. Decreasing subfoveal choroidal thickness and percentage of Sattler layer area were demonstrated in the progression of AMD. The choroidal change was related to atrophy of the microstructural changes of underlying capillaries and medium-sized vessels.